The mediating role of socio-economy on the relationship between customer lifestyles and the awareness of MobiCash banking services of Wahda Bank in Libya / Iman Elsalhen Bouthahaba and Mariam. M. Hassan Khaled - Bouthahaba, Iman Elsalhen; M. Hassan Khaled, Mariam. (Universiti Teknologi MARA, 2021)
The 2013-2014 liquidity crisis in Libya has resulted in many Libyans' difficulties accessing their banking accounts and managing their financial standing. In place of this, many commercial banks have developed new mobile payment techniques, particularly the 'MobiCash' Service offered by Wahda Bank to assist Libyan customers in accessing their accounts and carrying out their financial transactions. This paper intends to examine the effect of lifestyle changes on mobile banking services or 'MobiCash' and their awareness of this novel service. Also, this study investigates the more profound understanding of Libyan customers. It highlights customers' socioeconomic characteristics using 'MobiCash' services offered by Wahda Bank in the city of Derna in Libya. The questionnaires were distributed online, and a sample of 149 was obtained. SPSS was used to analyse the data and regression analysis to test the significant effect of customers' lifestyles and their awareness of 'MobiCash'. The results showed that Libyan customers were accepting of this form of mobile banking. The findings indicated that age and academic degrees do not influence awareness of 'MobiCash'. However, customer lifestyles affect awareness of the banking service of 'MobiCash'. Socio-Economic factors do not mediate the relationship between lifestyle and awareness of banking services of 'MobiCash'. This study's outcomes have increased the current knowledge on the behaviours and awareness of novel banking service features like 'MobiCash'. Moreover, the study may provide a more in-depth understanding of what is needed for Libyan banking customers to accept further this technological service and, thus, permit the improvement of banking strategies to attract potential users. Future researchers can extend the understanding of this study in other contexts and service environment.